Increasing the Students’ Writing Skill through Mind Mapping Technique - Khoiriyah, Khoiriyah (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2014)
This study is classroom action research implementing the use of mind mapping technique to improve the students’writing skill. The aim of this study is to identify whether mind mapping technique can improve students’ writing skill and describe the classroom situation when mind mapping is used in teaching and learning process of writing skill.The data were collected from 44 students of the first year students of English department at Nusantara PGRI Kediri University. The data compiled from the observation sheets on the lecturer’s and students’ performance done by the collaborator, field note made by the lecturer,questionnaire on the students and mainly the students’ achievement at the cycle test proved the mind mapping technique to be effective in improving the students’ writing skill. This study has been done into two cycles. The result of the study shows that the students’ mean score improved from the first cycle (70.95) to the second cycle (76.68). And out of 65.91% of the subjects got the target scores 75 in cycle I and it had been reached by 84.08% of the students in cycle II. In short, it can be concluded that in the last cycle, students had really made significant progress. The analyses resulted in the findings that mind mapping technique could improve the students’writing skill Key Words: Writing Skill, Mind Mapping.